Modified glass ionomer and orthodontic band: An interim alternative for the treatment of molar incisor hypomineralization. A case report - Orellana, Carla; Perez, Vidal (Journal of Oral Research, 2019)
Introduction: Molar incisor hypomineralization (MIH) is a developmental condition resulting in defects in the enamel characterized by demarcated opacities mainly affecting first permanent molars and occasionally permanent incisors in 1 of every 6 children worldwide. Affected molars have greater susceptibility to post eruptive breakdown, extensive caries and, in severe cases, are difficult to restore. When the MIH-affected molar presents severe crown destruction, it is necessary to perform an intermediate restoration to preserve the remaining dental structure in order to maintain occlusion, proper hygiene and periodontal health. The case of an 11-year-old patient with severe MIH is reported. The patient had extensive crown destruction by caries in tooth 1.6 without clinical or radiographic signs of pulp pathology. After an initial preventive intervention, enamel without dentin support and carious dentin were removed from tooth 1.6. Subsequently, crown restoration was performed with resin modified glass ionomer, followed by the cementation of an orthodontic band. After 18 months of follow-up, the patient reported no pain or discomfort. The restoration was preserved intact, maintaining occlusal functionality, pulp and gingival health. Conclusion: The interim treatment, cementing an orthodontic band over a tooth restored with glass ionomer seems to favor retention and compressive strength, keeping the MIH-affected molar asymptomatic for at least 18 months. Further studies evaluating this treatment option in similar clinical situations are recommended.